Adenoid cystic carcinoma of submandibular gland metastatic to great toes: case report and literature review. Issue 8 (20th July 2016) - Rafael, Oana C.; Paul, Doru; Chen, Sheng; Kraus, Dennis
Key Clinical Message: Adenoid cystic carcinoma (ACC) is a rare malignant tumor of the salivary glands, with higher frequency in the submandibular gland, a prolonged clinical course, and poor long‐term survival. It tends to metastasize to lungs, bone, liver, brain, and rarely to skin. Comprehensive skin examination and appropriate follow‐up is recommended, since cutaneous metastasis represents disease progression, requiring management and prognosis adjustment. Abstract : Adenoid cystic carcinoma (ACC) is a rare malignant tumor of the salivary glands, with higher frequency in the submandibular gland, a prolonged clinical course, and poor long‐term survival. It tends to metastasize to lungs, bone, liver, brain, and rarely to skin. Comprehensive skin examination and appropriate follow‐up is recommended, since cutaneous metastasis represents disease progression, requiring management and prognosis adjustment.